2006
DOI: 10.1124/mol.106.027458
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Nicotinic Cholinergic Receptors in Rat Superior Cervical and Nodose Ganglia

Abstract: Nicotinic cholinergic receptors (nAChRs) are present in ganglia in the peripheral nervous system. In autonomic ganglia, they are responsible for fast synaptic transmission, whereas in the sensory ganglia and sensory neurons, they may be involved in modulation of neurotransmission. The present study measured nAChRs in several rat autonomic ganglia: the superior cervical ganglia (SCG), sensory nodose ganglia, stellate ganglia, and pelvic ganglia. The densities of the heteromeric nAChRs determined by receptor bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 42 publications
3
79
2
1
Order By: Relevance
“…In the nodose ganglion, binding to nicotinic ligands amounts to about 10% of the binding in autonomic motor ganglia, being 85% of them β4* receptors and 15% β2* receptors. The subtype composition of these receptors is very similar to those expressed in autonomic motor ganglia, since α3β4 accounts for 50%, α3α5β4 for 35%, and α3β2β4 for 15% of receptors (Mao, Yasuda, Fan, Wolfe, & Kellar, 2006).…”
Section: Nociceptorsmentioning
confidence: 77%
See 1 more Smart Citation
“…In the nodose ganglion, binding to nicotinic ligands amounts to about 10% of the binding in autonomic motor ganglia, being 85% of them β4* receptors and 15% β2* receptors. The subtype composition of these receptors is very similar to those expressed in autonomic motor ganglia, since α3β4 accounts for 50%, α3α5β4 for 35%, and α3β2β4 for 15% of receptors (Mao, Yasuda, Fan, Wolfe, & Kellar, 2006).…”
Section: Nociceptorsmentioning
confidence: 77%
“…Immunochemical and functional studies in rodents have shown that ganglionic neurons express high levels of α3β4 receptors in the somatic/dendritic compartment along with two minor populations of α3α5β4 and α3β2β4 receptors with different physiological and pharmacological properties (David et al, 2010;Mao et al, 2006). Low levels of α4* nAChRs may be expressed during development (Scholze et al, 2011).…”
Section: Nachrs In Autonomic Motoneuronsmentioning
confidence: 99%
“…Finally, it is noteworthy that PeIA[S9H,V10A,E14N] is 1300-fold more potent at blocking ␣3␤2 than ␣3␤4 nAChRs. This exquisite selectivity for ␣3␤2 nAChRs may be useful for distinguishing between these two subtypes in neurons such as those found in intracardiac ganglia (Bibevski et al, 2000) and superior cervical ganglia (Mao et al, 2006; David et al, …”
Section: Discussionmentioning
confidence: 99%
“…Nicotine administered in vivo increases predominantly the ␣4␤2 nAChR subtype in the brain (1, 4); moreover, it does not increase the nAChRs in autonomic ganglia or adrenal gland (59,60), which appear to express predominantly ␣3␤4* nAChR subtypes and a smaller number of ␣3␤2* subtypes (61)(62)(63)(64). However, in mammalian cells transfected to heterologously express pairs of nAChR subunits that form potential receptor subtypes, exposure to nicotine for 3 days or longer increases […”
Section: Discussionmentioning
confidence: 99%
“…3 H]EB binding to several different subunit combinations, including ␣2␤2, ␣3␤2, ␣4␤2, ␣2␤4, ␣3␤4, and ␣4␤4 (27,37,64,65). Similarly, in the current studies, even a 24-h exposure of cells to either nicotine or carbachol increased almost all of the subtypes to some extent, with the ␣3␤4 subtype being the least affected (Table 1).…”
Section: Discussionmentioning
confidence: 99%